Hard duty - Turner, J. B. (Turner, J. B. Jon Reznick thriller, 2024)
"Black-ops specialist Jon Reznick is hoping for some well-earned down time under the Florida sun when he gets a surprise call from the CIA. An embittered US counterintelligence expert is about to sell a career's worth of state secrets to the Russians, and the Agency wants Reznick to track him down. With the spook holed up somewhere in the diplomatic cauldron of the Middle East, protected by highly trained Russian mercenaries, Reznick knows it's almost certainly a suicide mission. But with tough Scot Mac McCafferty and cybersecurity genius Trevelle Williams to back him up, patriot Reznick is soon racing across the region in pursuit of the target. Time is ticking and death is a strong possibility, but with stakes this high, for Jon Reznick there are no rules that can't be broken... and failure is never an option."--